Tempos narrativos e retrocesso temporal - Brenda Laca (Revista Linguística)
Starting from the observation that the Simple Past in languages such as French or Italian does not allow backshifting, a property that also generally characterizes the Historical Present, we provide a semantic analysis that accounts both for the similarities between those Simple Pasts and the Historical Present, and for the differences between the Simple Pasts of the French type and those of the English type. The analysis is bicontextual and follows the approach developed by Anand and Toosarvandani for the Historical Present. We further suggest that there is a correlation between Simple Pasts not permitting backshifting and the existence of aoristic Present Perfects. Keywords: Historical Present. Bicontextualism. Simple Past. Aoristic drift.